Regulatory Framework for Poultry Slaughterhouses: Case Study in Debotabek Area, Indonesia - Apriantini, A.; Adhi, A. K. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The increase of the community consumption of animal food origin, especially chicken, is continuing to rise. In the process of animal slaughter in slaughterhouse, there are the high numbers of fraudulence, which affect to the food security issues. Therefore, the government made the regulation not only the central government regulations but also the local government regulations regarding poultry slaughterhouse license in order to the poultry slaughterhouse could be operated with the standard of hygiene, food safety, halal matter, animal welfare, and not pollute and disrupt the environment. In addition to the existing of the permit of local governments, it is expected to do monitoring and controlling easier to the slaughterhouse in their territory. But, there are still many chicken carcass those are distributed on the market which are derived from illegal (does not have formal permission) poultry slaughterhouse so that the hygiene and the halal matter are doubtful. The purpose of this study is to find the obstacles in regulations of the building of poultry slaughterhouse, which led many slaughterhouse, especially small and medium sized slaughterhouse, and trouble in getting license of the building of slaughterhouse legally. It is to be expected that this research can be the input for the government in making  policy to ease the small and medium poultry slaughterhouse in legalizing their business. In addition, the research is expected to draw the situation and condition  to the stakeholders of poultry slaughterhouse about the procedures and regulations in the region, especially debotabek, in building of the industry of poultry slaughterhouse.